2017
DOI: 10.1016/j.cois.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of disease in bee foraging ecology

Abstract: Diseases have important but understudied effects on bee foraging ecology. Bees transmit and contract diseases on flowers, but floral traits including plant volatiles and inflorescence architecture may affect transmission. Diseases spill over from managed or invasive pollinators to native wild bee species, and impacts of emerging diseases are of particular concern, threatening pollinator populations and pollination services. Here we review how parasites can alter the foraging behaviour of bees by changing flora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 67 publications
(102 reference statements)
2
67
1
Order By: Relevance
“…Flowers can be visited by a wide range of pollinators and other species (McArt et al 2014) and are logical suspects as hotspots of pathogen transmission among bees, but very little empirical work has addressed this (reviewed in Koch et al 2017). More than 20 yr ago, a landmark study showed that Bombus terrestris could become infected with Crithidia by foraging on inflorescences previously foraged on by infected bees (Durrer and Schmid-Hempel 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Flowers can be visited by a wide range of pollinators and other species (McArt et al 2014) and are logical suspects as hotspots of pathogen transmission among bees, but very little empirical work has addressed this (reviewed in Koch et al 2017). More than 20 yr ago, a landmark study showed that Bombus terrestris could become infected with Crithidia by foraging on inflorescences previously foraged on by infected bees (Durrer and Schmid-Hempel 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, consuming the alkaloids nicotine and anabasine, found in Solanaceous plants, reduced infection by the gut pathogen Crithidia in the bumble bee Bombus impatiens at ecologically relevant concentrations (Richardson et al 2015). Given that some bee species have declined in recent years, due in part to pathogens (Potts et al 2010), and the largely unknown role of floral traits in pollinator-pathogen dynamics (McArt et al 2014, Koch et al 2017, it is critical to explore factors that influence flower-bee-pathogen interactions. Given that some bee species have declined in recent years, due in part to pathogens (Potts et al 2010), and the largely unknown role of floral traits in pollinator-pathogen dynamics (McArt et al 2014, Koch et al 2017, it is critical to explore factors that influence flower-bee-pathogen interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Wild B. terrestris colonies infected with C. bombi are less likely to produce new daughter queens compared with uninfected colonies (Goulson et al, 2017). Crithidia infection reduced queen colony founding success and colony size (Brown et al, 2003), and reduced motor learning rates of flower handling in B. impatiens (Gegear et al, 2005), which could influence how effectively bumble bees pollinate and forage (Koch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%